Cervical screening among Southern Alberta First Nations women living off-reserve - Jensen-Ross, Christine; University of Lethbridge. School of Health Sciences (Lethbridge, Alta. : University of Lethbridge, School of Health Sciences, 2006, 2006)
xii, 223 leaves 29 cm. First Nations women face nearly three times the risk of cervical cancer and mortality rates of up to six times higher than their non-Aboriginal counterparts. While cervical cancer is almost completely preventable, Southern Alberta First Nations women seldom access cervical screening services. The purpose of this qualitative focused ethnography was to gain an understanding of the cervical screening needs of un- and under-served First Nations women living off-reserve. Thirteen purposefully selected First Nations women participated in three focus groups utilizing semi-structured interviews. Personal self-worth and cervical screening awareness and relevance are essential to the pursuit of cervical screening. Barriers and incentives for screening and opportunities for acceptability and sustainability are explored. A holistic approach, intersectoral collaboration and cultural safety are described by focus group participants as foundational for optimal service delivery.